Evidence for Photocatalyst Involvement in Oxidative Additions of Nickel-Catalyzed Carboxylate O-Arylations - Malik, Jamal A. (J Am Chem Soc, 2020)
[Image: see text] Dual photocatalysis and nickel catalysis can effect cross-coupling under mild conditions, but little is known about the in situ kinetics of this class of reactions. We report a comprehensive kinetic examination of a model carboxylate O-arylation, comparing a state-of-the-art homogeneous photocatalyst (Ir(ppy)(3)) with a competitive heterogeneous photocatalyst (graphitic carbon nitride). Experimental conditions were adjusted such that the nickel catalytic cycle is saturated with excited photocatalyst. This approach was designed to remove the role of the photocatalyst, by which only the intrinsic behaviors of the nickel catalytic cycles are observed. The two reactions did not display identical kinetics. Ir(ppy)(3) deactivates the nickel catalytic cycle and creates more dehalogenated side product. Kinetic data for the reaction using Ir(ppy)(3) supports a turnover-limiting reductive elimination. Graphitic carbon nitride gave higher selectivity, even at high photocatalyst-to-nickel ratios. The heterogeneous reaction also showed a rate dependence on aryl halide, indicating that oxidative addition plays a role in rate determination. The results argue against the current mechanistic hypothesis, which states that the photocatalyst is only involved to trigger reductive elimination.